2020
DOI: 10.1371/journal.pone.0224118
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic factors associated with normal linear growth among pre-school children living in better-off households: A multi-country analysis of nationally representative data

Abstract: This study examined the socio-demographic factors associated with normal linear growth among pre-school children living in better-off households, using survey data from Ghana, Kenya, Nigeria, Mozambique and Democratic Republic of Congo (DRC). The primary outcome variable was child height-for-age z-scores (HAZ), categorised into HAZ�-2SD (normal growth/not stunted) and HAZ<-2 (stunted). Using logistic regression, we estimated adjusted odds ratios (aORs) of the factors associated with normal growth. Higher mater… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 49 publications
(71 reference statements)
4
15
4
Order By: Relevance
“…Stunting in children is also shown to be significantly associated with mothers' access to healthcare, as indicated by a sufficient number of ANC clinic visits (≥ 4 times). This is in line with previous studies (Amugsi et al, 2020;Budhathoki et al, 2020;Torlesse et al, 2016). Antenatal care is an important factor in ensuring healthy outcomes in women during pregnancy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Stunting in children is also shown to be significantly associated with mothers' access to healthcare, as indicated by a sufficient number of ANC clinic visits (≥ 4 times). This is in line with previous studies (Amugsi et al, 2020;Budhathoki et al, 2020;Torlesse et al, 2016). Antenatal care is an important factor in ensuring healthy outcomes in women during pregnancy.…”
Section: Discussionsupporting
confidence: 91%
“…Three studies in Ethiopia also found that mothers' educational level was associated with stunting in children aged 12 to 59 months (Takele et al, 2019), aged 6 to 59 months (Kahssay et al, 2020), and aged 5 to 59 months (Tariku et al, 2017). Maternal education is positively correlated with the healthy linear growth of children in several low-middle countries, such as Mozambique, Nigeria, Ghana, and Congo, but not Kenya (Amugsi et al, 2020). Increasing mothers' education level can improve their knowledge about breastfeeding, complementary feeding practices, and child growth.…”
Section: Discussionmentioning
confidence: 97%
“…We analysed the Demographic and Health Surveys (DHS) 38 data of poor households from Ghana, Kenya, Nigeria, Mozambique, and the Democratic Republic of Congo (DRC). The selection of the five countries was informed by our previous analysis using the same countries and data 39 41 . The DHS collects nationally representative data every five years in lower- and middle-income countries 42 , 43 .…”
Section: Methodsmentioning
confidence: 99%
“…We reclassified the child HAZ into not stunted (better growth) and stunted (poor growth). We defined children with HAZ above − 2 SD (HAZ > − 2SD) 41 , 49 , 51 as having a better linear growth/not stunted and described in this study as positive deviants. Similarly, children who had HAZ below − 2 SD (HAZ < − 2) from the median HAZ of the WHO reference population 49 were considered stunted or having poor growth 41 .…”
Section: Methodsmentioning
confidence: 99%
“…The association of malnutrition with fewer years of education of parents has also been previously described. In a study in Mozambique, Ghana, and Nigeria, children of parents with higher years of education were more likely to have adequate growth [44]. A study of stunting determinants in the Democratic Republic of Congo found an association of fewer years of education of mothers with stunting and access to safe water, sewage, and mother's BMI.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 98%